Brucella abortus impairs T lymphocyte responsiveness by mobilizing IL-1RA-secreting omental neutrophils - Joaquin M. Pellegrini; Gabriela González-Espinoza; Raheleh R. Shayan; Lisiena Hysenaj; Thomas Rouma; Vilma Arce-Gorvel; Hugues Lelouard; Dimitri Popoff; Yun Zhao; Sean Hanniffy; Amanda Castillo-Zeledón; Maite Loperena-Barber; et al. (Nature Communications)
Abstract Immune evasion strategies of Brucella, the etiologic agent of brucellosis, a global zoonosis, remain partially understood. The omentum, a tertiary lymphoid organ part of visceral adipose tissue, has never been explored as a Brucella reservoir. We report that B. abortus infects and replicates within murine omental macrophages. Throughout the chronic phase of infection, the omentum accumulates macrophages, monocytes and neutrophils. The maintenance of PD-L1+Sca-1+ macrophages, monocytes and neutrophils in the omentum depends on the wadC-encoded determinant of Brucella LPS. We demonstrate that PD-L1+Sca-1+ murine omental neutrophils produce high levels of IL-1RA leading to T cell hyporesponsiveness. These findings corroborate brucellosis patient analysis of whole blood displaying upregulation of PDL1 and Ly6E genes, and of serum exhibiting high levels of IL-1RA. Overall, the omentum, a reservoir for B. abortus, promotes bacterial persistence and causes CD4+ and CD8+ T cell immunosuppression by IL-1RA secreted by PD-L1+Sca-1+ neutrophils.